Association of 25-hydroxyvitamin D with all-cause and cardiovascular mortality among individuals with sarcopenia: evidence from the NHANES 2001–2006 - Chen Fu; Zhongxin Zhu; Yijie Mao; Wenjuan Wei (Frontiers in Nutrition)
BackgroundSarcopenia, defined as the progressive decline in muscular mass and physical power, poses significant health risks, particularly among aging populations.MethodsUtilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2001–2006, we employed multivariable Cox proportional hazards models to evaluate the relationship between serum 25-hydroxyvitamin D [25(OH)D] concentration and mortality outcomes, adjusting for multiple covariates. We additionally performed restricted cubic spline and threshold analyses using both linear and non-linear regression models to assess dose–response relationships and to explore the continuous effects of 25(OH)D on mortality outcomes. Stratified and sensitivity analyses were conducted to strengthen the reliability of our findings.ResultsA total of 1,666 participants diagnosed with sarcopenia were included in the analysis. Our results indicated a significant non-linear association between 25(OH)D concentration and both all-cause mortality and cardiovascular (CVD) mortality. Notably, threshold analyses revealed inflection points at 62.563 nmol/L for all-cause mortality and 47.367 nmol/L for CVD mortality, suggesting a plateau in protective effects at higher vitamin D levels. Both stratified and sensitivity analyses revealed no significant interactions across different subgroups.ConclusionThese findings emphasize the importance of maintaining adequate serum 25(OH)D concentration to mitigate mortality risk among sarcopenic individuals. Further research is needed to clarify the underlying mechanisms and to establish optimal vitamin D concentration for health benefits.